Changes in sea ice influence bowhead whale distribution and overlap with vessel transits in the Pacific Arctic - Angela R. Szesciorka; Justin A. Crawford; Greta Ferloni; Donna D. W. Hauser; Lori Quakenbush; Kathleen M. Stafford (Frontiers in Marine Science, 2026)
Introduction Arctic warming has resulted in substantial decreases in sea ice and a longer open-water season. This is occurring concurrently with changes in Bering-Chukchi-Beaufort bowhead whale seasonal movements and increasing vessel traffic through Bering Strait, which may increase strike risk. Methods To assess vessel traffic relative to bowhead whale distributions before (2013/14–2016/17), during (2017/18), and after (2018/19) a significantly low winter sea ice event in the Pacific Arctic, we combined vessel location data for eight vessel types during six seasons (September–March 2013–2019) transiting through whale utilization distributions (UDs) developed from satellite-linked telemetry from whales tagged during 2008–2019. Results Before the low ice event, the home range (95% UD) and core use area (50% UD) followed a consistent seasonal pattern of bowhead whales migrating south through the Chukchi Sea to wintering areas in the western Bering Sea. The UDs shifted northward during the low ice event, resulting in a decline in annual vessel transits through UDs, from an average of 234 transits in the 95% UD and 139 in the 50% UD during the four seasons before the event to 62 and 45 transits, respectively during the low ice event. Mean vessel speeds, however, increased from 7.2 to 8.7 kt in the 95% UD. After the event, UDs shifted southward, although not as far as before, and transits through UDs remained low (81 and 34) and at similar mean speeds (8.9 and 8.7 kt) than during the event. Discussion Regardless of period, vessels spent the most time along the northern coast of Chukotka and western Bering Sea resulting in the highest vessel densities and fastest mean vessels speeds. While it appears bowhead whales can adjust their distributions to rapidly changing ice conditions consequently overlapping with fewer vessels, faster transits through their UDs could put whales at increased risk of lethal strikes in the future.

Multiple Mechanisms Required to Predict Grass Community Composition - Jane A. Catford; Laura J. Graham; Harry E. R. Shepherd; Cindy E. Hauser; Nicola T. Munro; Brendan A. Wintle; John G. Donohue; David Tilman; Adam T. Clark (Ecology Letters, 2026)
Accurate prediction of community assembly is a central goal in ecology but is challenging because assembly is governed by numerous mechanisms. Few theoretical models explicitly incorporate or test multiple mechanisms at once. We empirically tested the predictive performance of a plant community assembly model built using all possible combinations of four ‘mechanisms’ (soil resource competition, dispersal and colonisation, spatiotemporal niche differentiation, population growth rates) and 11 underlying ‘attributes’ based on measured traits (e.g., fecundity, phenology). The full model accurately predicted out‐of‐sample biomass observations of five grasses sown in mixture along a soil nitrogen gradient (overall R 2 = 0.65). Alternative model variants, parameterised using subsets of the mechanisms and their nested attributes, still retained high explanatory power if the model included at least three of the four mechanisms. Our results suggest that plant community composition is determined by simultaneous effects of multiple mechanisms, and simpler theories have much lower predictive abilities.

Stratya2D: Enhancing kinematic backstripping through image-based 2D horizon integration - Harikrishnan Nalinakumar; Patrick Makuluni; Juerg Hauser; Stuart R. Clark (Computers & Geosciences, 2026)

Can compaction modeling and pore pressure prediction be simplified by the definition of effective stress? - Matt R. Hauser; Brent A. Couzens-Schultz (Marine and Petroleum Geology, 2025)

Rare phenotypes of white coat color in Simmental calves: genetic causes of syndromic forms of albinism and depigmentation - Joana G. P. Jacinto; Therese Leuenberger; Miriam Hauser; Irene M. Häfliger; Franz R. Seefried; Anna Letko; Cord Drögemüller (Molecular Genetics and Genomics, 2025)
The aim of this study was to investigate three unrelated Simmental calves with atypical white coat color, identify potential genetic causes using a trio-based whole-genome sequencing approach, and assess the prevalence of the identified variants in the breed. Several inherited alleles affecting coat color, ranging from fawn to red spotted and white-headed, have been described in Simmental cattle originating from Switzerland. However, no genetic variant has yet been associated with an almost completely white coat in this breed. Clinical examination revealed different syndromic disorders of white coat color in Simmental in all three cases, and pedigree records indicated recessive inheritance. Filtering for rare protein-changing variants revealed an independent homozygous variant that could be the cause in each case: a likely pathogenic missense variant in TYR (NP_851344.1:p.Pro428Leu) in case 1 with oculocutaneous albinism type 1, a likely pathogenic missense variant in GRID1 (XP_024842694.1:p.Pro489His) in case 2 with short stature-auditory depigmentation syndrome, and a frameshift variant of uncertain significance in RAD54B (NP_001179884.1:p.Ala722_Gly724delinsAsnLeuIlePheCys*) in case 3 with a multisystem depigmentation syndrome. Validation by Sanger sequencing confirmed the variant genotypes, and parental heterozygosity supported recessive inheritance. These variants were almost entirely absent from other breeds, and the allele frequency of the three candidate causal variants was less than 1% in the current Swiss Simmental population. This study identified three novel recessive alleles associated with syndromic forms of albinism or depigmentation, revealing unexpected heterogeneity. The investigation did not reveal any indications of possible dominant de novo mutations impacting protein coding genes including known candidate genes for depigmentation phenotypes. These findings possibly expand the list of pigmentation related genes in mammals, but further investigation is needed. We also highlight the biomedical relevance of investigating rare congenital disorders in livestock.

New occurrence record and dermal denticles of megamouth sharks from the Southwest Atlantic Coast - Lilian G. Xavier; Ana Kamila M. Lima; Emilio de C. Miguel; Salvatore Siciliano; Rachel Ann Hauser-Davis; Patricia do N. Bordallo; Georgia M. de O. Aragão; Jules M. R. Soto; João Eduardo P. de Freitas; Patricia Charvet; Vicente V. Faria (Environmental Biology of Fishes, 2025)

Accelerated transcriptomic age and susceptibility to traffic-related air pollution among cardiac catheterization patients - Thomas W. Jackson; Lydia Coulter Kwee; Svati H. Shah; Elizabeth R. Hauser; William E. Kraus; Cavin K. Ward-Caviness (Science of The Total Environment, 2025)

Cystathionine Gamma-Lyase: A Potential Longevity Gene Under Selection? - Gary J. Ren; Frances E. Hauser; Elissa Khodikian; Nathan R. Lovejoy; Cosima S. Porteus (Journal of Molecular Evolution, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evolution of rhodopsin in flatfishes (Pleuronectiformes) is associated with depth and migratory behavior - Esme S. B. Macpherson; Frances E. Hauser; Alexander Van Nynatten; Belinda S. W. Chang; Nathan R. Lovejoy (Journal of Fish Biology, 2024)
Visual signals are involved in many fitness‐related tasks and are therefore essential for survival in many species. Aquatic organisms are ideal systems to study visual evolution, as the high diversity of spectral properties in aquatic environments generates great potential for adaptation to different light conditions. Flatfishes are an economically important group, with over 800 described species distributed globally, including halibut, flounder, sole, and turbot. The diversity of flatfish species and wide array of environments they occupy provides an excellent opportunity to understand how this variation translates to molecular adaptation of vision genes. Using models of molecular evolution, we investigated how the light environments inhabited by different flatfish lineages have shaped evolution in the rhodopsin gene, which is responsible for mediating dim‐light visual transduction. We found strong evidence for positive selection in rhodopsin, and this was correlated with both migratory behavior and several fundamental aspects of habitat, including depth and freshwater/marine evolutionary transitions. We also identified several mutations that likely affect the wavelength of peak absorbance of rhodopsin, and outline how these shifts in absorbance correlate with the response to the light spectrum present in different habitats. This is the first study of rhodopsin evolution in flatfishes that considers their extensive diversity, and our results highlight how ecologically‐driven molecular adaptation has occurred across this group in response to transitions to novel light environments.

Microstructure development in lacustrine, fine-grained sediments traced by in situ and laboratory testing - S. Oberhollenzer; L. Hauser; A. Baldermann; R. Marte; F. Tschuchnigg; H. F. Schweiger; M. Nachtnebel; M. Dietzel (International Journal of Environmental Science and Technology, 2024)
Soil microstructure, often defined as the combination of particle arrangement and bonding, can strongly influence the stiffness and strength of sedimentary deposits. As undisturbed soil sampling is a challenging task in fine-grained soils, seismic in situ testing is becoming increasingly more important to investigate its mechanical behaviour. The aim of this article is to evaluate the influences of sediment depositional age and structure-forming processes on the degree of soil structure development in Alpine deposits. Seismic in situ and laboratory testing comprising X-ray diffraction (XRD), scanning electron microscopy (SEM), pore water chemical analysis and hydrochemical modelling were executed at three Austrian test sites, namely Lokalbahn Salzburg , Rhesi and water reservoir Raggal . Based on the comparison of in situ shear wave velocities ( V S, SDMT ) with bender element results ( V S, BE ), executed on reconstituted soil specimens, it is shown that the Pleisto–Holocene-aged deposits are characterized by a V S, BE / V S ,SDMT ratio of < 1, indicating the presence of microstructure. However, the youngest sediments (< 50 years) exhibit the weakest microstructure ( V S, BE / V S ,SDMT ≈ 1). The increase of soil structure with sediment age is represented by the updated normalized small-strain rigidity index, K * G , which is situated at the proposed transition between structured and unstructured soils ( K * G = 330), ranging between 250 and 350, at all test sites. The development of microstructure can be attributed to the precipitation of calcite (CaCO 3 ) cements in open pores, which strengthens the interparticle bonding between detrital quartz, feldspar, clay minerals and carbonate grains, subsequently reducing the soil`s porosity with increasing sediment age.

Multiple Ecological Axes Drive Molecular Evolution of Cone Opsins in Beloniform Fishes - Katherine D. Chau; Frances E. Hauser; Alexander Van Nynatten; Jacob M. Daane; Matthew P. Harris; Belinda S. W. Chang; Nathan R. Lovejoy (Journal of Molecular Evolution, 2024)

Infestation of cultivated Pacific oysters by shell-boring polychaetes along the US West Coast: Prevalence is associated with season, culture method, and pH - Julieta C. Martinelli; Megan Considine; Helen R. Casendino; Carolyn M. Tarpey; Isadora Jiménez-Hidalgo; Jacqueline L. Padilla-Gamiño; Teri L. King; Lorenz Hauser; Steven Rumrill; Chelsea L. Wood (Aquaculture, 2024)

Aligning theoretical and empirical representations of soil carbon-to-nitrogen stoichiometry with process-based terrestrial biogeochemistry models - Katherine S. Rocci; Cory C. Cleveland; Brooke A. Eastman; Katerina Georgiou; A. Stuart Grandy; Melannie D. Hartman; Emma Hauser; Hannah Holland-Moritz; Emily Kyker-Snowman; Derek Pierson; Peter B. Reich; Else P. Schlerman; et al. (Soil Biology and Biochemistry, 2024)

Fentanyl dysregulates neuroinflammation and disrupts blood-brain barrier integrity in HIV-1 Tat transgenic mice - Kara M. Rademeyer; Sara R. Nass; Austin M. Jones; Michael Ohene-Nyako; Kurt F. Hauser; MaryPeace McRae (Journal of NeuroVirology, 2024)

Pubertal progression in relation to peripubertal exposure to organochlorine chemicals in a cohort of Russian boys - Bora Plaku; Paige L. Williams; Oleg Sergeyev; Susan A. Korrick; Jane S. Burns; Jemar R. Bather; Russ Hauser; Mary M. Lee (International Journal of Hygiene and Environmental Health, 2023)

Longitudinal association of prepubertal urinary phthalate metabolite concentrations with pubertal progression among a cohort of boys - J.S. Burns; J.R. Bather; O. Sergeyev; M.M. Lee; S.A. Korrick; S. Sokolov; S. Kovalev; H.M. Koch; A.T. Lebedev; L. Mínguez-Alarcón; R. Hauser; P.L. Williams (Environmental Research, 2023)

Use of personal care products during pregnancy and birth outcomes – A pilot study - Marissa Chan; Emma V. Preston; Victoria Fruh; Marlee R. Quinn; Michele R. Hacker; Blair J. Wylie; Karen O'Brien; Paige L. Williams; Russ Hauser; Tamarra James-Todd; Shruthi Mahalingaiah (Environmental Research, 2023)

Novel infrastructure for coral gardening and reefscaping - Sebastian Schmidt-Roach; Rebecca Klaus; Abdulaziz M. Al-Suwailem; Alejandro R. Prieto; Julian Charrière; Charlotte A. E. Hauser; Carlos M. Duarte; Manuel Aranda (Frontiers in Marine Science, 2023)
Since 1950, coral abundance has declined worldwide by an estimated 60%, and further dramatic declines are predicted. Although global reductions in carbon emissions are essential to prevent further loss, coral reef restoration has become imperative to maintain the ecosystem services that coral reefs provide to humans at local scales. Yet, currently coral restoration and gardening efforts are too expensive to scale up due to the labor-intensive nature of the methods and low success rates. Here, we present a suite of technologies that improve coral reef restoration and rehabilitation’s scalability, efficiency, and effectiveness. Our modular technologies are designed to streamline in and ex situ nursery workflows, reduce maintenance times, solve problems in transporting corals to outplanting sites, and enable rapid outplanting on natural and artificial substrates. These novel structures can act as coral seeding hubs, which placed strategically, can have the capacity to enhance coral reproduction and replenish degraded nearby reefs with larvae. They can be applied to coral restoration and reefscaping, complemented by unique eco-friendly, low-carbon-emission structures for the creation of architecturally and visually appealing habitats and underwater landscapes. Our technologies integrate novel monitoring approaches that support intelligent solutions to track genotypes, optimize and control stock management, apply assisted evolution approaches, and adaptive management through long-term monitoring.

Before the Dam: A Fish-Mercury Contamination Baseline Survey at the Xingu River, Amazon Basin Before the Belo Monte Dam - J. Souza-Araujo; R. Andrades; R. A. Hauser-Davis; M. O. Lima; T. Giarrizzo (Bulletin of Environmental Contamination and Toxicology, 2022)

The relevance of pedigrees in the conservation genomics era - Stephanie J. Galla; Liz Brown; Yvette Couch‐Lewis (Ngāi Tahu: Te Hapū o Ngāti Wheke, Ngāti Waewae); Ilina Cubrinovska; Daryl Eason; Rebecca M. Gooley; Jill A. Hamilton; Julie A. Heath; Samantha S. Hauser; Emily K. Latch; Marjorie D. Matocq; Anne Richardson; et al. (Molecular Ecology, 2022)
Over the past 50 years conservation genetics has developed a substantive toolbox to inform species management. One of the most long‐standing tools available to manage genetics—the pedigree—has been widely used to characterize diversity and maximize evolutionary potential in threatened populations. Now, with the ability to use high throughput sequencing to estimate relatedness, inbreeding, and genome‐wide functional diversity, some have asked whether it is warranted for conservation biologists to continue collecting and collating pedigrees for species management. In this perspective, we argue that pedigrees remain a relevant tool, and when combined with genomic data, create an invaluable resource for conservation genomic management. Genomic data can address pedigree pitfalls (e.g., founder relatedness, missing data, uncertainty), and in return robust pedigrees allow for more nuanced research design, including well‐informed sampling strategies and quantitative analyses (e.g., heritability, linkage) to better inform genomic inquiry. We further contend that building and maintaining pedigrees provides an opportunity to strengthen trusted relationships among conservation researchers, practitioners, Indigenous Peoples, and Local Communities.

Glenn R. VanBlaricom † 1949–2020 - Alexandre N. Zerbini; Anthony J. Orr; Amanda L. Bradford; Michael Kenner; Robert Suydam; Carlos Alvarez‐Flores; Leah R. Gerber; Kristin Laidre; Donna Hauser; Laura Hoberecht (Marine Mammal Science, 2021)

Cytosolic and Metallothionein-Bound Hepatic Metals and Detoxification in a Sentinel Teleost, Dules auriga, from Southern Rio de Janeiro, Brazil - R. A. Hauser-Davis; D. R. Silva-Junior; A. R. Linde-Arias; M. Vianna (Biological Trace Element Research, 2021)

Regulation of the deleterious effects of binge-like exposure to alcohol during adolescence by α7 nicotinic acetylcholine receptor agents: prevention by pretreatment with a α7 negative allosteric modulator and emulation by a α7 agonist in alcohol-preferring (P) male and female rats - Zachary A. Rodd; Sheketha R. Hauser; H. Scott Swartzwelder; R. Aaron Waeiss; Debomoy K. Lahiri; Richard L. Bell (Psychopharmacology, 2020)

A Comprehensive Transcriptome Analysis Identifies FXN and BDNF as Novel Targets of miRNAs in Friedreich’s Ataxia Patients - Julia O. Misiorek; Anna M. Schreiber; Martyna O. Urbanek-Trzeciak; Magdalena Jazurek-Ciesiołka; Lauren A. Hauser; David R. Lynch; Jill S. Napierala; Marek Napierala (Molecular Neurobiology, 2020)
Friedreich’s ataxia (FRDA) is a genetic neurodegenerative disease that is caused by guanine-adenine-adenine (GAA) nucleotide repeat expansions in the first intron of the frataxin ( FXN ) gene. Although present in the intron, this mutation leads to a substantial decrease in protein expression. Currently, no effective treatment is available for FRDA, and, in addition to FXN , other targets with therapeutic potential are continuously sought. As miRNAs can regulate the expression of a broad spectrum of genes, are used as biomarkers, and can serve as therapeutic tools, we decided to identify and characterize differentially expressed miRNAs and their targets in FRDA cells compared to unaffected control (CTRL) cells. In this study, we performed an integrated miRNAseq and RNAseq analysis using the same cohort of primary FRDA and CTRL cells. The results of the transcriptome studies were supported by bioinformatic analyses and validated by qRT-PCR. miRNA interactions with target genes were assessed by luciferase assays, qRT-PCR, and immunoblotting. In silico analysis identified the FXN transcript as a target of five miRNAs upregulated in FRDA cells. Further studies confirmed that miRNA-224-5p indeed targets FXN, resulting in decreases in mRNA and protein levels. We also validated the ability of miRNA-10a-5p to bind and regulate the levels of brain-derived neurotrophic factor ( BDNF ), an important modulator of neuronal growth. We observed a significant decrease in the levels of miRNA-10a-5p and increase in the levels of BDNF upon correction of FRDA cells via zinc-finger nuclease (ZFN)-mediated excision of expanded GAA repeats. Our comprehensive transcriptome analyses identified miRNA-224-5p and miRNA-10a-5p as negative regulators of the FXN and BDNF expression, respectively. These results emphasize not only the importance of miRNAs in the pathogenesis of FRDA but also their potential as therapeutic targets for this disease.

Metal-Associated Biomarker Responses in Crabs from a Marine Protected Area in Southeastern Brazil - G. S. Araujo; P. K. Gusso-Choueri; D. I. T. Favaro; R. C. C. Rocha; T. D. Saint’Pierre; R. A. Hauser-Davis; B. Braz; R. E. Santelli; A. S. Freire; W. T. V. Machado; A. C. F. Cruz; D. M. S. Abessa (Archives of Environmental Contamination and Toxicology, 2020)

Genetic structure of endangered lake chubsucker Erimyzon sucetta in Canada reveals a differentiated population in a precarious habitat - Frances E. Hauser; João P. Fontenelle; Ahmed A. Elbassiouny; Nicholas E. Mandrak; Nathan R. Lovejoy (Journal of Fish Biology, 2019)
We used mitochondrial DNA to assess the genetic structure of endangered lake chubsucker Erimyzon sucetta across its Canadian range. We found unique mitochondrial haplotypes in Lyons Creek, a tributary of the Niagara River that faces a strong potential for habitat deterioration. Lyons Creek may therefore serve as a reservoir of unique genetic diversity. The sensitivity of Lyons Creek, combined with the genetic uniqueness of its E. sucetta population, call for further investigation into whether this population should be considered a separate designatable unit for conservation purposes.

Understanding the Scientific Basis of Post-traumatic Stress Disorder (PTSD): Precision Behavioral Management Overrides Stigmatization - Kenneth Blum; M. C. Gondré-Lewis; E. J. Modestino; L. Lott; D. Baron; D. Siwicki; T. McLaughlin; A. Howeedy; M. H. Krengel; M. Oscar-Berman; P. K. Thanos; I. Elman; et al. (Molecular Neurobiology, 2019)

Hepatic Metal and Metallothionein Levels in a Potential Sentinel Teleost, Dulesauriga, from a Southeastern Brazilian Estuary - R. A. Hauser-Davis; D. R. Silva-Junior; A. R. Linde-Arias; M. Vianna (Bulletin of Environmental Contamination and Toxicology, 2019)

Conditioned stimuli affect ethanol-seeking by female alcohol-preferring (P) rats: the role of repeated-deprivations, cue-pretreatment, and cue-temporal intervals - Sheketha R. Hauser; Gerald A. Deehan; Christopher P. Knight; Robert A. Waeiss; William A. Truitt; Philip L. Johnson; Richard L. Bell; William J. McBride; Zachary A. Rodd (Psychopharmacology, 2019)

HIV-1 Tat and opioids act independently to limit antiretroviral brain concentrations and reduce blood–brain barrier integrity - Crystal R. Leibrand; Jason J. Paris; Austin M. Jones; Quamrun N. Masuda; Matthew S. Halquist; Woong-Ki Kim; Pamela E. Knapp; Angela D. M. Kashuba; Kurt F. Hauser; MaryPeace McRae (Journal of NeuroVirology, 2019)

Therapeutic challenges for concurrent ethanol and nicotine consumption: naltrexone and varenicline fail to alter simultaneous ethanol and nicotine intake by female alcohol-preferring (P) rats - Robert A. Waeiss; Christopher P. Knight; Sheketha R. Hauser; Lauren A. Pratt; William J. McBride; Zachary A. Rodd (Psychopharmacology, 2019)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Selective breeding for high alcohol consumption and response to nicotine: locomotor activity, dopaminergic in the mesolimbic system, and innate genetic differences in male and female alcohol-preferring, non-preferring, and replicate lines of high-alcohol drinking and low-alcohol drinking rats - Gerald A. Deehan; Sheketha R. Hauser; Bruk Getachew; R. Aaron Waeiss; Eric A. Engleman; Christopher P. Knight; William J. McBride; William A. Truitt; Richard L. Bell; Zachary A. Rodd (Psychopharmacology, 2018)

Metal loads and biomarker suite responses in a tropical carnivorous fish indicative of anthropogenic impacts in a Southeastern Brazilian lagoon - R. S. C. Coimbra; M. S. Mascarenhas; V. B. Saraiva; C. R. Santos; R. M. Lopes; R. A. Hauser-Davis; V. P. S. Oliveira; M. M. Molisani; M. G. Almeida; C. E. Rezende; C. E. V. Carvalho; M. M. Oliveira (Environmental Monitoring and Assessment, 2018)

Migratory interchange of humpback whales (Megaptera novaeangliae) among breeding grounds of Oceania and connections to Antarctic feeding areas based on genotype matching - D. Steel; M. Anderson; C. Garrigue; C. Olavarría; S. Caballero; S. Childerhouse; P. Clapham; R. Constantine; S. Dawson; M. Donoghue; L. Flórez-González; N. Gibbs; et al. (Polar Biology, 2018)

Correction to: Cryptosporidium Spp. Contamination in Perna perna Mussels Destined for Human Consumption in Southeastern Rio de Janeiro, Brazil - A. L. Santos; L. T. F. de Oliveira; A. L. A. Souza; R. A. Hauser-Davis; S. G. De Simone (Bulletin of Environmental Contamination and Toxicology, 2018)

Cryptosporidium spp. Contamination in Perna perna Mussels Destined for Human Consumption in Southeastern Rio de Janeiro, Brazil - A. L. Santos; L. T. F. de Oliveira; A. L. A. Souza; R. A. Hauser-Davis; S. G. De Simone (Bulletin of Environmental Contamination and Toxicology, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Decadal shifts in autumn migration timing by Pacific Arctic beluga whales are related to delayed annual sea ice formation - Donna D. W. Hauser; Kristin L. Laidre; Kathleen M. Stafford; Harry L. Stern; Robert S. Suydam; Pierre R. Richard (Global Change Biology, 2017)
Migrations are often influenced by seasonal environmental gradients that are increasingly being altered by climate change. The consequences of rapid changes in Arctic sea ice have the potential to affect migrations of a number of marine species whose timing is temporally matched to seasonal sea ice cover. This topic has not been investigated for Pacific Arctic beluga whales ( Delphinapterus leucas ) that follow matrilineally maintained autumn migrations in the waters around Alaska and Russia. For the sympatric Eastern Chukchi Sea (‘Chukchi’) and Eastern Beaufort Sea (‘Beaufort’) beluga populations, we examined changes in autumn migration timing as related to delayed regional sea ice freeze‐up since the 1990s, using two independent data sources (satellite telemetry data and passive acoustics) for both populations. We compared dates of migration between ‘early’ (1993–2002) and ‘late’ (2004–2012) tagging periods. During the late tagging period, Chukchi belugas had significantly delayed migrations (by 2 to >4 weeks, depending on location) from the Beaufort and Chukchi seas. Spatial analyses also revealed that departure from Beaufort Sea foraging regions by Chukchi whales was postponed in the late period. Chukchi beluga autumn migration timing occurred significantly later as regional sea ice freeze‐up timing became later in the Beaufort, Chukchi, and Bering seas. In contrast, Beaufort belugas did not shift migration timing between periods, nor was migration timing related to freeze‐up timing, other than for southward migration at the Bering Strait. Passive acoustic data from 2008 to 2014 provided independent and supplementary support for delayed migration from the Beaufort Sea (4 day yr −1 ) by Chukchi belugas. Here, we report the first phenological study examining beluga whale migrations within the context of their rapidly transforming Pacific Arctic ecosystem, suggesting flexible responses that may enable their persistence yet also complicate predictions of how belugas may fare in the future.

Fish, genes and genomes: contributions to ecology, evolution and management - G. R. Carvalho; L. Hauser; J. Martinsohn; K. Naish (Journal of Fish Biology, 2016)

Co-administration of ethanol and nicotine: the enduring alterations in the rewarding properties of nicotine and glutamate activity within the mesocorticolimbic system of female alcohol-preferring (P) rats - Gerald A. Deehan; Sheketha R. Hauser; R. Aaron Waeiss; Christopher P. Knight; Jamie E. Toalston; William A. Truitt; William J. McBride; Zachary A. Rodd (Psychopharmacology, 2015)

Reduction of alcohol drinking of alcohol-preferring (P) and high-alcohol drinking (HAD1) rats by targeting phosphodiesterase-4 (PDE4) - Kelle M. Franklin; Sheketha R. Hauser; Amy W. Lasek; Jeanette McClintick; Zheng-Ming Ding; William J. McBride; Richard L. Bell (Psychopharmacology, 2015)

Insights from 20 years of bacterial genome sequencing - Miriam Land; Loren Hauser; Se-Ran Jun; Intawat Nookaew; Michael R. Leuze; Tae-Hyuk Ahn; Tatiana Karpinets; Ole Lund; Guruprased Kora; Trudy Wassenaar; Suresh Poudel; David W. Ussery (Functional & Integrative Genomics, 2015)

Ethanol and nicotine interaction within the posterior ventral tegmental area in male and female alcohol-preferring rats: evidence of synergy and differential gene activation in the nucleus accumbens shell - William A. Truitt; Sheketha R. Hauser; Gerald A. Deehan; Jamie E. Toalston; Jessica A. Wilden; Richard L. Bell; William J. McBride; Zachary A. Rodd (Psychopharmacology, 2015)

Hypothesis-independent pathway analysis implicates GABA and Acetyl-CoA metabolism in primary open-angle glaucoma and normal-pressure glaucoma - Jessica N. Cooke Bailey; Brian L. Yaspan; Louis R. Pasquale; Michael A. Hauser; Jae H. Kang; Stephanie J. Loomis; Murray Brilliant; Donald L. Budenz; William G. Christen; John Fingert; Douglas Gaasterland; Terry Gaasterland; et al. (Human Genetics, 2014)

Enhanced alcohol-seeking behavior by nicotine in the posterior ventral tegmental area of female alcohol-preferring (P) rats: modulation by serotonin-3 and nicotinic cholinergic receptors - Sheketha R. Hauser; Gerald A. Deehan; Jamie E. Toalston; Richard L. Bell; William J. McBride; Zachary A. Rodd (Psychopharmacology, 2014)

Population-specific home ranges and migration timing of Pacific Arctic beluga whales (Delphinapterus leucas) - Donna D. W. Hauser; Kristin L. Laidre; Robert S. Suydam; Pierre R. Richard (Polar Biology, 2014)

Investigations and design of pyridine-2-carboxylic acid thiazol-2-ylamide analogs as methionine aminopeptidase inhibitors using 3D-QSAR and molecular docking - Potshangbam Angamba Meetei; Alexander S. Hauser; Prathigadapa S. Raju; R. S. Rathore; N. Prakash Prabhu; Vaibhav Vindal (Medicinal Chemistry Research, 2014)

Providing patient education: impact on quantity and quality of family health history collection - Chris A. Beadles; R. Ryanne Wu; Tiffany Himmel; Adam H. Buchanan; Karen P. Powell; Elizabeth Hauser; Vincent C. Henrich; Geoffrey S. Ginsburg; Lori A. Orlando (Familial Cancer, 2014)

Bisphenol A concentrations in maternal breast milk and infant urine - K. Mendonca; R. Hauser; A. M. Calafat; T. E. Arbuckle; S. M. Duty (International Archives of Occupational and Environmental Health, 2014)

Genome-wide association study and meta-analysis of intraocular pressure - A. Bilge Ozel; Sayoko E. Moroi; David M. Reed; Melisa Nika; Caroline M. Schmidt; Sara Akbari; Kathleen Scott; Frank Rozsa; Hemant Pawar; David C. Musch; Paul R. Lichter; Doug Gaasterland; et al. (Human Genetics, 2014)

Gene–smoking interactions in multiple Rho-GTPase pathway genes in an early-onset coronary artery disease cohort - Cavin Ward-Caviness; Carol Haynes; Colette Blach; Elaine Dowdy; Simon G. Gregory; Svati H. Shah; Benjamin D. Horne; William E. Kraus; Elizabeth R. Hauser (Human Genetics, 2013)

Secondary contact and changes in coastal habitat availability influence the nonequilibrium population structure of a salmonid ( O ncorhynchus keta ) - E. L. Petrou; L. Hauser; R. S. Waples; J. E. Seeb; W. D. Templin; D. Gomez‐Uchida; L. W. Seeb (Molecular Ecology, 2013)
Numerous empirical studies have reported lack of migration–drift equilibrium in wild populations. Determining the causes of nonequilibrium population structure is challenging because different evolutionary processes acting at a variety of spatiotemporal scales can produce similar patterns. Studies of contemporary populations in northern latitudes suggest that nonequilibrium population structure is probably caused by recent colonization of the region after the last P leistocene ice age ended ~13 000 years ago. The chum salmon's ( O ncorhynchus keta ) range was fragmented by dramatic environmental changes during the P leistocene. We investigated the population structure of chum salmon on the N orth A laska P eninsula ( NAP ) and, using both empirical data and simulations, evaluated the effects of colonization timing and founder population heterogeneity on patterns of genetic differentiation. We screened 161 single nucleotide polymorphisms and found evidence of nonequilibrium population structure when the slope of the isolation‐by‐distance relationship was examined at incremental spatial scales. In addition, simulations suggested that this pattern closely matched models of recent colonization of the NAP by secondary contact. Our results agree with geological and archaeological data indicating that the NAP was a dynamic landscape that may have been more recently colonized than during the last deglaciation because of dramatic changes in coastal hydrology over the last several thousand years.

Polybrominated Diphenyl Ethers (PBDES) and Polychlorinated Biphenyls (PCBS) in Mussels and Two Fish Species from the Estuary of the Guanabara Bay, Southeastern Brazil - S. F. Gonçalves da Silva; I. M. R. A. Brüning; R. C. Montone; S. Taniguchi; M. J. Cascaes; P. S. Dias; R. C. Lavandier; R. A. Hauser-Davis; I. Moreira (Bulletin of Environmental Contamination and Toxicology, 2013)

Relationship between effective population size, inbreeding and adult fitness‐related traits in a steelhead ( O ncorhynchus mykiss ) population released in the wild - K. A. Naish; T. R. Seamons; M. B. Dauer; L. Hauser; T. P. Quinn (Molecular Ecology, 2013)
Inbreeding is of concern in supportive breeding programmes in Pacific salmonids, Oncorhynchus spp, where the number of breeding adults is limited by rearing space or poor survival to adulthood, and large numbers are released to supplement wild stocks and fisheries. We reconstructed the pedigree of 6602 migratory hatchery steelhead ( O ncorhynchus mykiss ) over four generations, to determine the incidence and fitness consequences of inbreeding in a northwest USA programme. The hatchery maintained an effective population size, = 107.9 from F 0 to F 2 , despite an increasing census size ( N ), which resulted in a decreasing N e / N ratio (0.35 in F 0 to 0.08 in F 2 ). The reduced ratio was attributed to a small broodstock size, nonrandom transfers and high variance in reproductive success (particularly in males). We observed accumulation of inbreeding from the founder generation (in F 4 , percentage individuals with inbreeding coefficients Δf > 0 = 15.7%). Generalized linear mixed models showed that body length and weight decreased significantly with increasing Δf , and inbred fish returned later to spawn in a model that included father identity. However, there was no significant correlation between Δf and age at return, female fecundity or gonad weight. Similarly, there was no relationship between Δf and reproductive success of F 2 and F 3 individuals, which might be explained by the fact that reproductive success is partially controlled by hatchery mating protocols. This study is one of the first to show that small changes in inbreeding coefficient can affect some fitness‐related traits in a monitored population propagated and released to the wild.

Alterations in Morphometric and Organosomatic Indices and Histopathological Analyses Indicative of Environmental Contamination in Mullet, Mugil liza, from Southeastern Brazil - R. A. Hauser-Davis; R. C. Lavandier; F. F. Bastos; T. F. Oliveira; C. A. Oliveira Ribeiro; R. L. Ziolli; R. C. de Campos (Bulletin of Environmental Contamination and Toxicology, 2012)

A Pneumocystis jirovecii pneumonia outbreak in a single kidney-transplant center: role of cytomegalovirus co-infection - R. U. Pliquett; A. Asbe-Vollkopf; P. M. Hauser; L. L. Presti; K. P. Hunfeld; A. Berger; E. H. Scheuermann; O. Jung; H. Geiger; I. A. Hauser (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

The stimulating effects of ethanol on ventral tegmental area dopamine neurons projecting to the ventral pallidum and medial prefrontal cortex in female Wistar rats: regional difference and involvement of serotonin-3 receptors - Zheng-Ming Ding; Scott M. Oster; Sarah R. Hall; Eric A. Engleman; Sheketha R. Hauser; William J. McBride; Zachary A. Rodd (Psychopharmacology, 2011)

Polymorphic variants in tenascin-C (TNC) are associated with atherosclerosis and coronary artery disease - Mollie A. Minear; David R. Crosslin; Beth S. Sutton; Jessica J. Connelly; Sarah C. Nelson; Shera Gadson-Watson; Tianyuan Wang; David Seo; Jeffrey M. Vance; Michael H. Sketch; Carol Haynes; Pascal J. Goldschmidt-Clermont; et al. (Human Genetics, 2011)

Validation and efficacy of transgenerational mass marking of otoliths in viviparous fish larvae - M. Kuroki; R. M. Buckley; L. L. LeClair; L. Hauser (Journal of Fish Biology, 2010)
Transgenerational mass marking of viviparous fish larvae in vivo was validated by intra‐muscular injection of elemental strontium chloride (SrCl 2 ) in gestating females and detection of the Sr in the otoliths of developing larvae. All otoliths of brown rockfish Sebastes auriculatus larvae produced from SrCl 2 ‐injected females showed enriched Sr:Ca ratios near the otolith edges, and the signatures did not appear to be affected by the anterior, centre and posterior positions of larvae within the ovary. Results from the present study indicate that transgenerational marking is a highly reliable technique for marking large numbers of extremely small viviparous fish larvae.

Genetic variation in the IL7RA/IL7 pathway increases multiple sclerosis susceptibility - Rebecca L. Zuvich; Jacob L. McCauley; Jorge R. Oksenberg; Stephen J. Sawcer; Philip L. De Jager; Cristin Aubin; Anne H. Cross; Laura Piccio; Neelum T. Aggarwal; Denis Evans; David A. Hafler; Alastair Compston; et al. (Human Genetics, 2010)

Effects of egg size, parental origin and feeding conditions on growth of larval and juvenile cod Gadus morhua - H. Paulsen; O. S. Kjesbu; V. Buehler; R. A. J. Case; C. Clemmesen; G. Carvalho; L. Hauser; W . F. Hutchinson; E. Moksness; H. OTTERå; A. Thorsen; T. SVåSAND (Journal of Fish Biology, 2009)
An experimental study was performed to disentangle parental and environmental effects on the growth of Atlantic cod Gadus morhua larvae and juveniles. Eggs were collected during the spawning season from spawning pairs (families) kept separately in specially designed spawning compartments. Newly hatched larvae were released simultaneously into two mesocosms of 2500 and 4400 m 3 . Larval growth was monitored by sampling over a 10 week period, after which juveniles were transferred to on‐growing tanks, where they were tagged and kept for up to 2 years. Maternal origin was determined by individual microsatellite genotyping of the larvae ( n = 3949, 24 families) and juveniles ( n = 600). The results showed significant positive correlations between egg size and larval size during the whole mesocosm period. Correlations, however, weakened with time and were no longer significant at the first tank‐rearing sampling at an age of 9 months. Significant family‐specific differences in growth were observed. The coefficient of variation ( c.v. ) was calculated in order to examine variation in standard length of larvae during the mesocosm period. Inter‐family c.v. was on average 69% of intra‐family c.v. Differences in zooplankton densities between the two mesocosms were reflected in larval growth, condition factor and c.v. Low food abundance appeared to reduce c.v. and favour growth of larvae that showed relatively slow growth at high food abundance. It is suggested that genetically determined variation in growth potential is maintained by environmental variability.

Spontaneous gene flow and population structure in wild and cultivated chicory, Cichorium intybus L. - L. P. Kiær; F. Felber; A. Flavell; R. Guadagnuolo; D. Guiatti; T. P. Hauser; A. M. Olivieri; I. Scotti; N. Syed; M. Vischi; C. van de Wiel; R. B. Jørgensen (Genetic Resources and Crop Evolution, 2009)

Genetic effects in the leukotriene biosynthesis pathway and association with atherosclerosis - David R. Crosslin; Svati H. Shah; Sarah C. Nelson; Carol S. Haynes; Jessica J. Connelly; Shera Gadson; Pascal J. Goldschmidt-Clermont; Jeffery M. Vance; Jason Rose; Chris B. Granger; David Seo; Simon G. Gregory; et al. (Human Genetics, 2009)

Editorial - Lorenz Hauser; Robin S. Waples; Gary R. Carvalho (Fish and Fisheries, 2008)

Paradigm shifts in marine fisheries genetics: ugly hypotheses slain by beautiful facts - Lorenz Hauser; Gary R Carvalho (Fish and Fisheries, 2008)
By providing new approaches to the investigation of demographic and evolutionary dynamics of wild populations, molecular genetics has led to fundamental changes in our understanding of marine ecology. In particular, genetic approaches have revolutionized our understanding in three areas: (i) most importantly, they have contributed to the discovery of extensive genetic population structure in many marine species, overturning the notion of large, essentially homogenous marine populations limiting local adaptation and speciation. (ii) Concomitant differences in ecologically important traits now indicate extensive adaptive differentiation and biocomplexity, potentially increasing the resilience to exploitation and disturbance. Evidence for rapid adaptive change in many populations underlies recent concerns about fisheries‐induced evolution affecting life‐history traits. (iii) A compilation of recent published research shows estimated effective population sizes that are 2–6 orders of magnitude smaller than census sizes, suggesting more complex recruitment dynamics in marine species than previously assumed. Studies on Atlantic cod are used to illustrate these paradigm shifts. In our synthesis, we emphasize the implications of these discoveries for marine ecology and evolution as well as the management and conservation of exploited marine fish populations. An important implication of genetic structuring and the potential for adaptive divergence is that locally adapted populations are unlikely to be replaced through immigration, with potentially detrimental consequences for the resilience to environmental change – a key consideration for sustainable fisheries management.

Susceptibility of wild carrot (Daucus carota ssp. carota) to Sclerotinia sclerotiorum - B. D. Jensen; M. R. Finckh; L. Munk; T. P. Hauser (European Journal of Plant Pathology, 2008)

Magnetic resonance imaging in spinocerebellar ataxias - Susanne Döhlinger; Till-Karsten Hauser; Johannes Borkert; Andreas R. Luft; Jörg B. Schulz (The Cerebellum, 2008)

Validation of operational AVHRR subpixel snow retrievals over the European Alps based on ASTER data - N. Foppa; A. Hauser; D. Oesch; S. Wunderle; R. Meister (International Journal of Remote Sensing, 2007)

The temporal development in a hybridizing population of wild and cultivated chicory ( Cichorium intybus L.) - B. S. SØRENSEN; L. P. KIÆR; R. B. JØRGENSEN; T. P. HAUSER (Molecular Ecology, 2007)
Hybridization and its possible impacts is a subject of increased attention in connection with the risk of unintended gene flow from cultivated (including genetically modified) plants to wild relatives. Whether such gene flow by hybridization is likely to take place depends among other things on the persistence of the hybrids in a natural environment over time. To evaluate this, we studied an experimental hybridizing population of wild and cultivated chicories ( Cichorium intybus ) relative to a previous study on the same population 2 years earlier. We compared the genetic composition, morphology and fitness traits of plants from 2004 to the plants in the same plot in 2002. The majority of the plants in 2004 was more morphologically and genetically intermediate than in 2002. This indicates that no selection towards being wild‐like or cultivar‐like was present over the period of 2 years. Furthermore, no distinct fitness differences existed between the plants of 2004, probably due to most of the plants being intermediate. No hybridization barriers appeared to be present between wild and cultivated chicories beyond the F 1 generation, since F 2 hybrids and backcrosses were in abundance; in fact, hybrids of probably fourth or fifth generation were present. In conclusion, all results indicate that no barriers exist to the temporal persistence of chicory hybrids in a natural environment.

Hierarchical population genetic structure in the commercially exploited shrimp Crangon crangon identified by AFLP analysis - D. Weetman; A. Ruggiero; S. Mariani; P. W. Shaw; A. R. Lawler; L. Hauser (Marine Biology, 2007)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

An empirical verification of population assignment methods by marking and parentage data: hatchery and wild steelhead ( Oncorhynchus mykiss ) in Forks Creek, Washington, USA - L. HAUSER; T. R. SEAMONS; M. DAUER; K. A. NAISH; T. P. QUINN (Molecular Ecology, 2006)
Assignment tests are increasingly applied in ecology and conservation, although empirical comparisons of methods are still rare or are restricted to few of the available approaches. Furthermore, the performance of assignment tests in cases with low population differentiation, violations of Hardy–Weinberg equilibrium and unbalanced sampling designs has not been verified. The release of adult hatchery steelhead to spawn in Forks Creek in 1996 and 1997 provided an opportunity to compare the power of different assignment methods to distinguish their offspring from those of sympatric wild steelhead. We compared standard assignment methods requiring baseline samples (frequency, distance and Bayesian) and clustering approaches with and without baseline information, using six freely available computer programs. Assignments were verified by parentage data obtained for a subset of returning offspring. All methods provided similar assignment success, despite low differentiation between wild and hatchery fish ( F ST = 0.02). Bayesian approaches with baseline data performed best, whereas the results of clustering methods were variable and depended on the samples included in the analysis and the availability of baseline information. Removal of a locus with null alleles and equalizing sample sizes had little effect on assignments. Our results demonstrate the robustness of most assignment tests to low differentiation and violations of assumptions, as well as their utility for ecological studies that require correct classification of different groups.

Heterogeneous evolution of microsatellites revealed by reconstruction of recent mutation history in an invasive apomictic snail, Potamopyrgus antipodarum - David Weetman; Lorenz Hauser; Gary R. Carvalho (Genetica, 2006)

Impact of Opiate–HIV-1 Interactions on Neurotoxic Signaling - Kurt F. Hauser; Nazira El-Hage; Shreya Buch; Avindra Nath; William R. Tyor; Annadora J. Bruce-Keller; Pamela E. Knapp (Journal of Neuroimmune Pharmacology, 2006)

Design and validation of a partial-genome microarray for transcriptional profiling of the Bradyrhizobium japonicum symbiotic gene region - F. Hauser; A. Lindemann; S. Vuilleumier; A. Patrignani; R. Schlapbach; H.M. Fischer; H. Hennecke (Molecular Genetics and Genomics, 2006)

Molecular targets of opiate drug abuse in neuro AIDS - Kurt F. Hauser; Nazira El-Hage; Shreya Buch; Joseph R. Berger; William R. Tyor; Avindra Nath; Annadora J. Bruce-Keller; Pamela E. Knapp (Neurotoxicity Research, 2005)

Variability in condition and growth of Atlantic cod larvae and juveniles reared in mesocosms: environmental and maternal effects - C. Clemmesen; V. Bühler; G. Carvalho; R. Case; G. Evans; L. Hauser; W. F. Hutchinson; O. S. Kjesbu; H. Mempel; E. Moksness; H. Otteraa; H. Paulsen; et al. (Journal of Fish Biology, 2003)
Standard length, dry mass and RNA : DNA ratio measurements of 3876 Atlantic cod Gadus morhua larvae and juveniles from 26 families of recruit (fish during their first year of spawning) and repeat spawners (fish which were in their subsequent spawning season) reared in two mesocosms (2500 and 4400 m 3 ) under semi‐natural conditions were analysed over a period of 10 weeks using microsatellites. Larvae from recruit spawners were significantly longer and heavier at hatch and throughout the 10 weeks. RNA : DNA ratios from recruit spawner offspring were only significantly higher at week 1. The smaller (2500 m 3 ) mesocosm was characterized by low plankton density during the transition from endogenous to exogenous feeding followed by a higher density during the metamorphosis period (weeks 4 and 5), with the reverse pattern evident in the 4400 m 3 mesocosm. Patterns of larval growth followed patterns of zooplankton density. Significant differences in RNA : DNA ratios between the mesocosms at all comparable sampling dates were found and within each mesocosm individual fish exhibited a wide range of growth and condition responses under the same environmental conditions. RNA : DNA ratios as a function of size differed in the amount of variability between mesocosms, indicating that the higher food density led to a higher proportion of well‐conditioned larvae in the first 3 weeks. Food availability probably has a major role in determining offspring growth and condition, with limited effects due to maternal effects in cases where the broodstock females are approximately of similar size and condition.

Performance of a maize/cassava intercrop in tilled and no-till Senna spectabilis alley cropping on an Ultisol in southern Cameroon - S. Hauser; J. N. Ndi; N. R. Hulugalle (Agroforestry Systems, 2000)

Yields of maize/cassava intercrops grown with hedgerows of three multipurpose trees on an acid Ultisol of Cameroon - S. Hauser; J. N. Ndi; N. R. Hulugalle (Agroforestry Systems, 2000)

Screening of DNA polymorphisms in samples of archived scales from New Zealand snapper - G. J. Adcodk; J. H. Bernal Ramázrez; L. Hauser; P. Smith; G. R. Carvalho (Journal of Fish Biology, 2000)
Primers and protocols were developed to screen effciently DNA sequence polymorphism of nuclear and mitochondrial loci in samples of dried archived scales collected over the last 50 years from the New Zealand snapper Pagrus auratus (Sparidae).

CC-chemokine receptor 5 polymorphism and age of onset in familial multiple sclerosis - L. F. Barcellos; A. M. Schito; J. B. Rimmler; E. Vittinghoff; A. Shih; R. Lincoln; S. Callier; M. K. Elkins; D. E. Goodkin; J. L. Haines; M. A. Pericak-Vance; S. L. Hauser; et al. (Immunogenetics, 2000)

Nitrogen and phosphorus uptake by maize as affected by particulate organic matter quality, soil characteristics, and land-use history for soils from the West African moist savanna zone - B. Vanlauwe; K. Aihou; S. Aman; B. K. Tossah; J. Diels; O. Lyasse; S. Hauser; N. Sanginga; R. Merckx (Biology and Fertility of Soils, 2000)

A- or C-chromosomes, does it matter for the transfer of transgenes from Brassica napus - J. Tomiuk; T. P. Hauser; R. Bagger-Jørgensen (Theoretical and Applied Genetics, 2000)

Parental contribution and coefficient of coancestry among maize inbreds: pedigree, RFLP, and SSR data - R. Bernardo; J. Romero-Severson; J. Ziegle; J. Hauser; L. Joe; G. Hookstra; R. W. Doerge (Theoretical and Applied Genetics, 2000)

Molecular markers and the species concept: New techniques to resolve old disputes? - Gary R. Carvalho; Lorenz Hauser (Reviews in Fish Biology and Fisheries, 1999)

Genetic population structure in the Lake Tanganyika sardine Limnothrissa miodon - L. Hauser; G. R. Carvalho; T. J. Pitcher (Journal of Fish Biology, 1998)
There was significant morphological differentiation among samples of Tanganyika sardine Limnothrissa miodon , indicating non‐random association of fish. Individuals within schools appeared to be unrelated as high mtDNA haplotype diversity demonstrated the presence of many maternal lineages in each school. Nevertheless, there was evidence from allozyme analysis for genetic differentiation on a very small geographical scale, possibly even among individual schools, without any clear geographical boundaries among populations. Similar microgeographical differentiation at the allozyme level was found in several marine pelagic species, suggesting a general pattern of random genetic structure in pelagic schooling fish. Such genetic patchiness may arise from biased reproductive success in localized spawning events and long‐term stability of schools, resulting in genetic differentiation among schools. While the present results are preliminary, the far‐reaching implications both for fisheries management and for evolutionary processes in pelagic species warrant further research on microgeographical genetic patterns using more sensitive markers.

Isolation and characterization of a mutant protoporphyrinogen oxidase gene from Chlamydomonas reinhardtii conferring resistance to porphyric herbicides - Barbara L. Randolph-Anderson; Ryo Sato; Anita M. Johnson; Elizabeth H. Harris; Charles R. Hauser; Kenji Oeda; Fumiharu Ishige; Shoichi Nishio; Nicholas W. Gillham; John E. Boynton (Plant Molecular Biology, 1998)

Genetic affinities of an introduced predator: Nile perch in Lake Victoria, East Africa - L. HAUSER; G. R. CARVALHO; TONY J. PITCHER; RICHARD OGUTU‐OHWAYO (Molecular Ecology, 1998)
Although the introduction of Nile perch, Lates niloticus , to Lake Victoria has received intense global attention, especially in relation to its impact on endemic cichlid species and on fishery yields, fundamental information on its taxonomy and population genetics is lacking. Most importantly, the introduced fish originated from two lakes (Lakes Albert and Turkana) containing three Lates species, and it has never been entirely clear which of these became established in Lake Victoria, or indeed whether the Lake Victoria population is derived from hybridization between Lates species. In addition, genetic drift caused by the relatively small founder population (≈ 400), the initially slow population increase followed by a period of explosive population growth, and selection pressures in the new environment may have resulted in substantial genetic changes. Allozyme data indicated that the introduced Nile perch of Lake Victoria were mainly L. niloticus from Lake Albert, although maximum likelihood estimates of stock contributions (GSI) suggested the presence of L. macrophthalmus. In contrast, introduced Nile perch in adjacent smaller lakes (Lakes Kyoga and Nabugabo) appeared to be entirely L. niloticus . The effect of the introductions on allozyme diversity varied among lakes and appeared to be uncorrelated to the number of fish introduced.

Low Specificity of the Bacterial Index for the Diagnosis of Bacterial Pneumonia by Bronchoalveolar Lavage - R. Speich; M. Hauser; T. Hess; J. Wst; E. Grebski; F. H. Kayser; E. W. Russi (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Low specificity of the bacterial index for the diagnosis of bacterial pneumonia by bronchoalveolar lavage - R. Speich; M. Hauser; T. Hess; J. Wüst; E. Grebski; F. H. Kayser; E. W. Russi (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Predation by the desert pupfish,Cyprinodon macularius onCulex mosquitoes and benthic chironomid midges - E. F. Legner; R. A. Medved; W. J. Hauser (BioControl, 1975)